The Adrenocortical Response to Synthetic ACTH Following a Trek to High Altitude - Mackey, J.; Mellor, A.; Watchorn, J.; Burnett, A.; Boot, C.; Woods, D. (Hormone and Metabolic Research, 2016)
Gradual ascent to high altitude is typically associated with reduced resting aldosterone and unchanged cortisol, features that may facilitate acclimatization but are poorly understood. The aim of the study was to investigate the cortisol and aldosterone response to adrenocorticotrophic hormone at altitude. Eleven subjects underwent a 250 μg short synacthen test at sea-level and again after trekking to 3 600 m in Nepal. Cortisol and aldosterone were measured by conventional assay from blood samples taken immediately prior to the administration of synacthen (T0) and then 30 (T30) and 60 (T60) min later. At 3 600 m resting basal cortisol and aldosterone levels were both significantly lower than they were at sea-level (p=0.004, p=0.003, respectively). Cortisol values at T30 and T60 were not different between sea-level and 3 600 m but the increment after synacthen was significantly greater (p=0.041) at 3 600 m due to a lower basal value. Aldosterone at T30 and T60 was significantly lower (p=0.003 for both) at 3 600 m than at sea-level and the increment following synacthen was also significantly less (p=0.003) at 3 600 m. At 3 600 m there appears to be a divergent adrenal response to synthetic adrenocorticotrophic hormone with an intact cortisol response but a reduced aldosterone response, relative to sea-level. This may reflect a specific effect of hypoxia on aldosterone synthesis and may be beneficial to acclimatization.
Keywords: high altitude; hypoxia; cortisol; aldosterone; synacthen; ACTH